Simulation analysis of ultrasonic testing in steel-based butt weld joint - Mukhtar, Muhammad Faiz Hakimi; Mahmod, M. F. (Penerbit UTHM, 2021)
Within this study, a simulation analysis based on Ultrasonic Testing (UT) is made using Comsol Multiphysics. Comsol Multiphysics is a software that can simplify many aspects of building UT method and also can be used to obtain a fast understanding of the results of altering the fundamental parameters. The software program has useful features which can help in technique development especially for UT inspectors in Non- destructive Testing (NDT) field. The focus of this study is to conduct a simulation analysis of internal weld defects by developing the model of defects in a weld structure sample configured using the software. The model is developed based on actual parameters and characterization of weld structure sample and internal weld defects. The results of analysis show that each type of defects which are incomplete penetration, slag inclusion and lack of fusion have different signal pattern and signal amplitude which are depended on the characterizations of those defects themselves.